KEPEMIMPINAN TRANSFORMATIF SEBAGAI MODEL PENGEMBANGAN SUMBER DAYA MANUSIA YANG KREATIF - Mahirun Mahirun; Suryani Suryani; Nur Baiti Nasution (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
A leader is someone with certain softskill ability which can’t replaced by machine. Therefore, in this 4.0 revolution industries era a leader should keep their ability to solve every leadership problem and develop creative human resource. This study aims to develop a conseptual theory of transformational leadership as a basic framework to implement the development of creative human resources in organizations. A  comprehensive analysis was used to explain some popular leadership styles, such as transformational leadership style, transactional leadership style, charismatic leadership styles and literature on innovation and creativity for the development of human resource empowerment models. Results revealed that the concept of transformative leadership for a creative human resource development model is a process of managing the creativity of human resources that prioritizes credibility by developing new ideas that are unique and unusual, have benefits by changing the nature, function or condition, also converting to achieve organizational goals.